2012
DOI: 10.5720/kjcn.2012.17.2.226
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between High Energy/Low Nutrient Food Consumption and Obesity among Korean Children and Adolescents

Abstract: Consumption of foods with high energy and low nutrient values has been linked to various health issues including obesity and chronic diseases. This study investigated the high-energy/low-nutrient food consumption status and its relationship with obesity status and intake of energy and nutrients, using the Korea National Health and Nutrition Examination Survey (KNHANES) and the Korea Youth Risk Behavior Web-based Survey (KYRBWS). The prevalence of overweight and obesity among 2-18 year-olds was 8.4% and 10.8% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The percentages of those who consumed fruits three times a day were also below 4% in both years. As this distribution was considered inadequate to analyze vegetable and fruit consumption based on three times a day, this study reclassified '1-3 times of food consumption per day' into 'Once or more a day (≥ 1/day)' as in the study of Heo et al [ 19 ]. From the 2006 survey, 'Once in 6-7 days', 'Once in 4-5 days', 'Once in 2-3 days', and 'Not consumed at all in the past week' were re-coded into 'Less than once a day (< 1/day).'…”
Section: Methodsmentioning
confidence: 99%
“…The percentages of those who consumed fruits three times a day were also below 4% in both years. As this distribution was considered inadequate to analyze vegetable and fruit consumption based on three times a day, this study reclassified '1-3 times of food consumption per day' into 'Once or more a day (≥ 1/day)' as in the study of Heo et al [ 19 ]. From the 2006 survey, 'Once in 6-7 days', 'Once in 4-5 days', 'Once in 2-3 days', and 'Not consumed at all in the past week' were re-coded into 'Less than once a day (< 1/day).'…”
Section: Methodsmentioning
confidence: 99%
“…A study by Moon and Lee [13] on youth obesity found that people consumed more soda, fruits, fast food, instant noodles, and snacks in the underweight group than in the obese group, while studies by Heo, Nam, Lee and Chung [14] also showed lower levels of consuming soda and instant noodles in the obese group than in the non-obese group. Studies on physical activity showed that the more physical activity decreased, the lower the rate of participation in school physical education classes in adolescents in obese groups [15] and the lower the rate of the obese group exercising compared to non-obese groups was, in particular, the great difference was in muscle-strengthening movements [13].…”
Section: Introductionmentioning
confidence: 98%
“…Peers influence adolescents’ diet and PA behaviors in other countries, and could be important targets for modifying diet and PA to prevent or reduce adolescent obesity in Korea. However, the effects of peers on Korean adolescents’ diet and PA behaviors have not been studied (Heo, Nam, Lee, & Chung, ; Song et al., ), and studies in Western countries may not be relevant. Studies examining associations between Korean adolescents’ diets and PA and those of their peers could support culturally appropriate interventions.…”
mentioning
confidence: 99%